Drug use, testing, and treatment in local jails - Wilson, Doris James (Bureau of Justice Statistics)
Describes the drug involvement of jail inmates and the level of drug use, testing, and treatment in jails. This report is the third in a series on prior drug use and treatment of offenders, and uses data from the 1998 Annual Survey of Jails and the 1996 Survey of Inmates in Local Jails. (See also Substance Abuse and Treatment, State and Federal Prisoners, 1997 and Substance Abuse and Treatment of Adults on Probation, 1995.) Data in this report are presented on the number of jurisdictions that conduct drug tests on jail inmates and staff, the criteria for testing, the percent of tests on jail inmates that are positive for drugs, and policies and actions taken by jurisdictions in response to positive tests. Other data describe the type of treatment programs available in local jail jurisdictions and the number of inmates in treatment on June 30, 1998. The report also summarizes the characteristics of drug-involved jail inmates, including their drug use history, criminal history, and participation in treatment since admission.